Impact of Green Marketing on Urban Sustainable Development (A Study of Consumers’ Perspectives in Charikar City, Afghanistan) - Hazheer, Abdul Wali; Ramin, Enayatullah (ORGANIZE: Journal of Economics, Management and Finance, 2026)
Green marketing is defined as a modern marketing strategy which, through increasing the level of consumers’ awareness, attitudes, and behavior toward environmentally friendly products, can contribute to reducing pollution, improving waste management, and enhancing the quality of urban life. This research was conducted with the aim of examining the impact of green marketing on urban sustainable development from the viewpoint of consumers in Charikar City, Parwan Province. The statistical population included all residents of the city, and data were collected from 200 individuals through random sampling using a Likert-scale questionnaire. The reliability of the collected data was confirmed using Cronbach’s alpha. Pearson correlation and multiple regression tests were applied for data analysis. The findings of the Pearson test indicate weak relationships and correlations among the variables, which further emphasizes the importance of multivariate analysis. Moreover, the regression results show that the level of consumer awareness has a positive and significant effect on urban sustainable development, while green attitudes and green purchasing behavior do not have a direct impact on the main variable. The overall results indicate that increasing awareness of green marketing can play a pivotal role in achieving indicators of urban sustainable development, while other components are effective only through interaction with awareness and the provision of access to green products.